The Evolution Of Natural Language Processing - Kakadiya, Fena; Usadadiya, Deep; Gohil, Raj; Vyas, Akshay; Karia, Harsh; Golakiya, Nil; Kharade, Sonali (Journal of Neonatal Surgery, 2025)
Natural Language Processing (NLP) has emerged as a pivotal field within artificial intelligence, enabling machines to understand and generate human language. This paper provides an all-inclusive overview of NLP, detailing its definitions, historical evolution, key techniques, applications, current trends, challenges, and future directions. By examining the dual pillars of Natural Language Understanding (NLU) and Natural Language Generation (NLG), we highlight the significant Development made in the field while also addressing the ethical considerations and challenges that persist. The paper concludes with a discussion on the future of NLP, emphasizing the need for enhanced contextual understanding and cross-lingual capabilities.